Incidence of Candidemia in Neutropenia with Administration of Broad-Spectrum Antibiotics in Pediatric Patients with Acute Lymphoblastic Leukemia - Ratridewi, Irene; Chrishariyati, Cahyani; Winaputri, Savitri Laksmi; Nugroho, Susanto (Indonesian Journal of Tropical and Infectious Disease, 2024)
Candidemia is one of the main causes of morbidity and mortality in patients with hematological malignancies. However, the difficulty in establishing a definitive diagnosis causes these high rates. Therefore, a rapid diagnosis process is needed for the early stages of infection as the initial clinical management in pediatric patients with malignancy, especially accompanied by neutropenia. This study aims to determine the risk factors for candidemia in children using PCR (Polymerase Chain Reaction). A cross-sectional study design was used to determine the relationship between neutropenia and broad-spectrum antibiotics with the incidence of candidemia in pediatric patients with acute lymphoblastic leukemia (ALL). The results were analyzed statistically. 33 pediatric patients who met the inclusion criteria, 22 (66.67%) were positive for candida. The sample was dominated by male (66.67%) with a mean age of 4.5 years and had undergone the standard (14 patients) and high-risk (19 patients) chemotherapy protocols. The correlation test revealed no significant correlation between the administration of broad-spectrum antibiotics and the incidence of candidemia in pediatric patients with ALL (p= 0.052), neutropenia recorded a notable relationship to those patients (p=0.033). This study shows that neutropenia is a risk factor that affects the prevalence of candidemia in pediatric patients with ALL. Children with ALL who have severe neutropenia are at an increased risk of developing candidemia.